Pengaruh Proporsi Jamur Tiram Putih (Pleurotus ostreatus) Terhadap Kandungan Protein, Kalsium dan Daya Terima Bakso Jamur - Nany Suryani; Maulidah Maulidah; Ristiyanti Rahayu; STIKES Husada Borneo; RSUD dr. H. Moch. Ansari Saleh Banjarmasin; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Food sources of vegetable protein can be used as a food sources of protein such as mushrooms, mushrooms have high enough protein and calcium content. Mushrooms can be processed into a variety of dishes, one of them is in making meatballs. This study aims to analyze the content of protein, calcium and acceptance mushroom meatballs. This study is experimental with five treatments consisting of P1 comparison of white oyster mushroom : beef (100gr : 0gr), P2 ratio of white oyster mushroom : beef (75gr : 25gr), P3 comparison of white oyster mushroom : beef (50gr : 50gr), P4 ratio of white oyster mushroom : beef (25gr : 75gr) and P5 comparison of white oyster mushroom : beef (0gr : 100gr). Protein content is tested using kjedahl method, the content of calcium is tested using titration methods, and acceptance is tested using the hedonic method 30 conducted on consumer panelists. The statistical test of protein and calcium uses oneway ANOVA and the statistic test of acceptance uses friedman test. The obtained the results of the study, there is an effect on the proportion of white oyster mushroom protein content in mushroom meatballs (p = 0,001), there is an effect on the proportion of white oyster mushroom calcium content in mushrooms meatballs (p = 0,000), there is an effect the proportion of white oyster mushroom on acceptance flavor (p = 0,000), taste (p = 0,001) and texture (p = 0,000), but no effect of oyster mushrooms on the acceptance color (p = 0,420) in the mushroom meatballs. Expected to grow oyster mushrooms (Pleurotus ostreatus) as a basic material for making meatballs mushrooms, because of its nutrient content is high. P3 has a very high content of protein and not much different from the protein content on P5, so that it can be used as an entrepreneurship for meatball merchant.